CLINICAL EVALUATION METHODS OF ODONTOGENIC PHLEGMONS IN PEDIATRIC PATIENTS - Akhmedov Ilham Ibrahimovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This study explores the clinical characteristics and evaluation methods of odontogenic phlegmons in pediatric patients. Odontogenic phlegmons—rapidly progressing, diffuse purulent inflammations of the soft tissues—are frequently encountered in the maxillofacial region of children due to the high prevalence of untreated dental infections. The immature immune response and anatomical features in children often lead to more rapid progression and higher risk of systemic complications. This article presents findings from a clinical study conducted on 54 pediatric patients aged 3 to 15 years, focusing on the localization, clinical presentation, diagnostic parameters, and assessment criteria used to classify the severity of the condition. Based on clinical, laboratory, and radiological data, a comprehensive approach to evaluate and manage odontogenic phlegmons in children is proposed. The implementation of these methods in clinical practice can significantly improve early diagnosis, guide treatment strategies, and reduce complications.